Introduction to Banach Spaces: Analysis and Probability - Daniel LI, Herve Queffelec (New York Cambridge University Press, 2018)
School of Mathematics and Natural Science
MIR No: 190
Order Date: 2024-07-08
Order No: CU/OPEX/LIBRARY/24/2024-25
Received Date: 2024-10-22
Keywords: Mathematics, Banach Spaces